2005
DOI: 10.1002/mus.20306
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral axon caliber and conduction velocity are decreased after burn injury in mice

Abstract: Peripheral neuropathies are reported to arise as a result of the systemic inflammatory response produced by a full-thickness cutaneous burn injury. This study was designed to characterize the magnitude and time course of functional and morphological changes in peripheral axons that arise after a full-thickness dermal burn injury in an animal model. A 20% body surface area (20% BSA) full-thickness dermal burn was applied to the back of C57BL6 female mice. Longitudinal H- and M-wave recordings were used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…For example, peripheral axon caliber and conduction velocity have been found to decrease after burn injury. 54 Despite such important peripheral damages, however, the present findings support the hypothesis stating that MI helps keeping the motor program active, thus priming and facilitating the future execution of movements by improving neuronal plasticity and preserving motor functions. 27 Thus, the implementation of a guided MI framework within conventional therapy seems to be a promising substitute and/or complement to executed movements to activate some compensatory networks for motor rehabilitation.…”
Section: Discussionsupporting
confidence: 82%
“…For example, peripheral axon caliber and conduction velocity have been found to decrease after burn injury. 54 Despite such important peripheral damages, however, the present findings support the hypothesis stating that MI helps keeping the motor program active, thus priming and facilitating the future execution of movements by improving neuronal plasticity and preserving motor functions. 27 Thus, the implementation of a guided MI framework within conventional therapy seems to be a promising substitute and/or complement to executed movements to activate some compensatory networks for motor rehabilitation.…”
Section: Discussionsupporting
confidence: 82%
“…In rats, histological evaluation of nerve fibers following burn injury have shown Wallerian degeneration of axons, disintegration of the myelin sheath, and degeneration of the motor end plate. 36,37 A decrease in the caliber of large axons have been demonstrated with histological studies. 36,37 Furthermore, increased platelet aggregation, accelerated fibrin deposition, and clot formation have been shown to occur following burn injury, leading to vascular occlusion of the vasa nervorum.…”
Section: Mechanismmentioning
confidence: 86%
“…36,37 A decrease in the caliber of large axons have been demonstrated with histological studies. 36,37 Furthermore, increased platelet aggregation, accelerated fibrin deposition, and clot formation have been shown to occur following burn injury, leading to vascular occlusion of the vasa nervorum. 38,39 Additional studies have demonstrated that cutaneous burns induce the release of large molecules from damaged epidermal and dermal cells, which increases interstitial oncotic pressure and stimulates fluid loss leading to edema formation.…”
Section: Mechanismmentioning
confidence: 86%
“…In general, the MNCV reflects the conduction velocity of the myelinated fibers that have the maximum diameter (Waxman, 1980;Higashimori et al, 2005). The mean axon diameter of the F-and P-nerve groups was significantly greater than that of the UW-nerve group; however there was no significant difference in the MNCV among the groups.…”
Section: Discussionmentioning
confidence: 97%